2020
DOI: 10.1136/bmjopen-2020-038474
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomised controlled trial evaluating the effects of the orexin receptor antagonist suvorexant on sleep architecture and delirium in the intensive care unit

Abstract: IntroductionInsomnia frequently occurs in patients admitted to an intensive care unit (ICU). Sleep-promoting agents may reduce rapid eye movement sleep and have deliriogenic effects. Suvorexant (Belsomra) is an orexin receptor antagonist with Food and Drug Administration (FDA) approval for the treatment of adult insomnia, which improves sleep onset and maintenance as well as subjective measures of quality of sleep. This trial will evaluate the efficacy of postoperative oral suvorexant treatment on night-time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…[4][5][6] Awareness regarding risk factors, prevention, and diagnosis of postoperative delirium has grown substantially in recent years. [7][8][9] There are equivocal data on the association between intraoperative blood pressure management and the incidence of postoperative delirium. [10][11][12][13] A critical decrease in cerebral perfusion pressure, for example, during cardiac arrest is an independent risk factor for delirium.…”
mentioning
confidence: 99%
“…[4][5][6] Awareness regarding risk factors, prevention, and diagnosis of postoperative delirium has grown substantially in recent years. [7][8][9] There are equivocal data on the association between intraoperative blood pressure management and the incidence of postoperative delirium. [10][11][12][13] A critical decrease in cerebral perfusion pressure, for example, during cardiac arrest is an independent risk factor for delirium.…”
mentioning
confidence: 99%
“…[18][19][20]25,26,29,31,32 Suvorexant and other orexin receptor antagonists are also important candidates for ICU sleep research given they have been found to be beneficial for chronic insomnia, may help prevent delirium, and have a relatively benign safety profile. 47,48…”
Section: Discussionmentioning
confidence: 99%
“…However, the study of pharmacologic options to promote nighttime sleepiness is limited by small trial sizes, the failure to enroll mechanically ventilated adults with a high severity of illness, and an overreliance on delirium reduction and/or patient-reported sleep quality to define efficacy. In addition, RCTs to date have involved prescribing of pharmacologic agents upon ICU admission or timed in relation to specific clinical events (e.g., surgical procedure) ( 222 224 ). However, in practice, clinicians are frequently seeking options to promote sleep after patients report sleep disruption or have already presented with delirium.…”
Section: Subtopic 4: Treatment Of Icu Scdmentioning
confidence: 99%